Engineering of nanostructured plasmonic substrates for use as SERS sensors (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2017)
Plasmonic nanostructures strongly localize electric fields on their surfaces via the collective oscillations of conducting electrons under stimulation by incident light at certain wavelength. Molecules adsorbed onto such surfaces experiences a strongly enhanced electric field due to the localized surface plasmon resonance (LSPR), which amplifies the Raman scattering signal from these molecules. This phenomenon is referred to as surface enhanced Raman scattering (SERS). Further enhancements in the Raman intensity have been achieved by designing plasmonic nanostructures with a controlled size, shape, composition, and arrangement. This review paper focuses on the theory and analyses the influence of protective coating with oxide materials an isolated plasmonic metal nanostructures. Starting with a brief description of the basic principles underlying LSPR and SERS, we compare two plasmonic metals, two dielectric materials and the effect of changing individual parameters of the nanostructure on output enhanced Raman signal.